How Organizations Constitute Technological Visions to Navigate Uncertain Futures - Saaoud, Elie; Rampa, Romain; Agogué, Marine (Tecnoscienza – Italian Journal of Science & Technology Studies, 2024)
Emerging technologies are characterized by malleability and incompleteness, rendering them profoundly unpredictable. Science and Technology Studies (STS) have underscored the significance of prospective narratives, such as technological visions, in managing the inherent uncertainty of emerging technologies. However, the dynamics of prospective narratives within the settings of organizations remain underexplored in organizational studies (OS). Therefore, this paper explores the mechanism by which organizations frame emerging technologies and navigate the future’s intrinsic uncertainty. We investigate these issues through an ethnographic case study of EnerCo, a large electricity utility. We find that the process of constitution of a technological vision is driven by iterative enactments of anticipating, which involves creatively formulating prospective narratives, and disseminating, which encompasses transferring and translating prospective narratives into new social settings. By bridging the STS literature on technological expectation and the OS practice framework of zoom in/out, we offer a fresh outlook on the reciprocal relationship between organizational dynamics and technoscientific narratives.